'On Heroes, Hero-Worship, and the Heroic' in Environmental History. (1st May 2004) - Wynn, Graeme
Abstract : George Perkins Marsh is both the hero and the foil of this paper. His well-known book, Man and Nature, and his reputation as the fountainhead of the conservation movement lie at the very centre of the story offered here. But this account also casts some doubt upon the precedence generally attributed to some of Marsh's ecological claims, and questions the wisdom of placing Marsh and other historical figures on pedestals that elevate them too readily and too markedly above their peers. It does this by probing the reception of Marsh's ideas in New Zealand in the 1870s, by considering the ideas of largely-forgotten Titus Smith about human impacts upon the vegetation of Nova Scotia in the nineteenth century, and by wondering about the implications of these tales of environmental understanding from two colonial realms for the practice of environmental history in the twenty-first century. This is thus both an engagement with Marsh and a story about stories, about how they are constructed, about how they travel and about how they influence the ways in which historians present the past and speak to the future.